ANALYSIS OF FACTORS CONTRIBUTING TO STUNTING INCIDENCE AMONG TODDLERS IN SOUTH SOLOK DISTRICT - Fransisca, Dewi; Fernando, Fenny; Pebrina, Melia; Hayu, Ramah (E-Jurnal Medika Udayana, 2024)
Stunting, or short stature in children, is a condition of chronic malnutrition in early childhood that occurs during the period of growth and development in early life. Inadequate nutritional intake during infancy can lead to growth failure and a decrease in intelligence. This condition will further reduce individual productivity, thus impacting the decline in the quality of human resources. The objective of this study is to determine the factors associated with stunting incidence among toddlers aged 24-59 months in the Work Area of Muara Labuh Community Health Center, South Solok District, in 2022. This is an analytical study with a case-control design. The population consists of mothers with stunted toddlers aged 24-59 months, totaling 64 individuals as cases, and mothers with non-stunted toddlers aged 24-59 months, totaling 64 individuals as controls, with a total of 128 individuals sampled using total sampling technique. Statistical analysis was conducted using the chi-square test. Half (50%) of the toddlers experienced stunting, more than half of the respondents (63.8%) did not provide exclusive breastfeeding, more than half of the respondents (65.6%) had a history of infectious diseases, and less than half (45.3%) had a history of chronic energy deficiency (CED) status. The obtained p-values were 0.001, 0.000, and 0.000, respectively. There is a relationship between exclusive breastfeeding, history of infectious diseases, and maternal nutritional status during pregnancy with stunting incidence. Health workers should provide counseling on the factors causing stunting so that prevention efforts and interventions can be implemented against risk factors.